2017
DOI: 10.4103/1793-5482.215765
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stereotactic and ultrasound-guided biopsy of solid supratentorial tumor: A preliminary report

Abstract: Introduction:The computed tomography (CT) guided stereotactic biopsy (STB) is considered as method of choice for biopsy of intracranial mass lesions. However, it's disadvantages are frame fixation, time requirement for transportation between CT scan suit to the operation theater with added much higher equipment cost in the relatively resource scarred developing country. Ultrasound-guided biopsy (USGB) is relatively simpler, economical, less time consuming, and real-time procedure.Clinical Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…For deep-seated "difficult" lesions, it is likely that the operating surgeon preferred to use NUS due to its theoretical advantages. Again, the results were in accordance to those reported in the literature, with significant hematoma formation in 4%-5% of cases and neurological worsening in 5%-13% of cases [5,11,12]. Using the duplex mode of US for delineation of the vessels, a safe trajectory can be determined for biopsy.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…For deep-seated "difficult" lesions, it is likely that the operating surgeon preferred to use NUS due to its theoretical advantages. Again, the results were in accordance to those reported in the literature, with significant hematoma formation in 4%-5% of cases and neurological worsening in 5%-13% of cases [5,11,12]. Using the duplex mode of US for delineation of the vessels, a safe trajectory can be determined for biopsy.…”
Section: Discussionsupporting
confidence: 88%
“…Based on an extensive search of the literature, to the best of our knowledge, no study has yet compared free-hand 2DUS-guided and navigated 3DUS-guided biopsies. In both groups, the diagnostic yield was comparable (FUS, 93.26%; NUS, 91.67%; overall, 92.8%), and in accordance with previous series of IOUS-guided biopsies in the literature [5,11,12,14]. Allouch et al [5] reported one of the largest series of US-guided biopsies.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations